2019
DOI: 10.3389/fmicb.2019.01953
|View full text |Cite
|
Sign up to set email alerts
|

Set-Up of Bacterial Cellulose Production From the Genus Komagataeibacter and Its Use in a Gluten-Free Bakery Product as a Case Study

Abstract: The use of bacterial cellulose (BC) in food systems is still limited due to production costs. Nine clones belonging to Komagataeibacter hansenii, Komagataeibacter nataicola, Komagataeibacter rhaeticus, Komagataeibacter swingsii, and Komagataeibacter xylinus species were screened for cellulose productivity in growth tests with five different carbon sources and three nitrogen sources. The water-holding and rehydration capacities of the purified cellulose were determined. The structure of the polymer was investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 64 publications
0
23
0
Order By: Relevance
“…As indicated in Fig. 9, all FT-IR spectra displayed peaks around 3350 cm -1 to 3400 cm -1 , and around 2900 cm -1 , indicating the presence of hydrogenbonded -OH groups of cellulose and the presence of amorphous cellulose, respectively (Fu and Liu 2011;Vigentini et al 2019) (Table 3). These peaks confirmed that the chemical structure of BC remained unchanged after entrapping proteins such as SPI and MP.…”
Section: Surface Analyses Of Bc Bio-leathersmentioning
confidence: 94%
“…As indicated in Fig. 9, all FT-IR spectra displayed peaks around 3350 cm -1 to 3400 cm -1 , and around 2900 cm -1 , indicating the presence of hydrogenbonded -OH groups of cellulose and the presence of amorphous cellulose, respectively (Fu and Liu 2011;Vigentini et al 2019) (Table 3). These peaks confirmed that the chemical structure of BC remained unchanged after entrapping proteins such as SPI and MP.…”
Section: Surface Analyses Of Bc Bio-leathersmentioning
confidence: 94%
“…Exopolysaccharides (EPS) are biopolymers of high molecular weight produced by several microorganisms, such as LAB, AAB and microalgae [68][69][70].…”
Section: Exopolysaccharidesmentioning
confidence: 99%
“…Among the HoPS, dextran, levan, and cellulose are mostl important in the food industry for their significant features [71,72]. In particular, EPS-producing LAB are attractive for application in bakery products thanks to their ability as viscosifiers, texturizers, emulsifiers, and syneresis-lowering agents [62,70]. In addition to polysaccharides naturally occurring in cereal grains flour and dough, microbial EPS from sucrose can be produced in sourdough through the activity of glycosyltransferases [73].…”
Section: Exopolysaccharidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellulose generated by Komagataeibacter spp. can be a valuable resource for the food industry in compliance with the current legislation of some countries, e.g., the FDA considers BC as GRAS (Vigentini et al, 2019). Nevertheless, the EFSA (European Food Safety Authority) scientific panel has not decided yet on this issue, in spite of the fact that the chemical structure of BC is well known and identical to that of the vegetable cellulose.…”
Section: Kombucha Microbial Community Biosafety: What Is Known From Our Shared History On Earthmentioning
confidence: 99%